2013
DOI: 10.1016/j.ecolind.2012.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater sediment pesticide biodegradation potential as an ecological indicator of microbial recovery following a decrease in chronic pesticide exposure: A case study with the herbicide diuron

Abstract: The aim of this study was to evaluate the use of freshwater sediment biodegradation potential as an ecological indicator for monitoring microbial recovery following a decrease in chronic pesticide exposure. For this purpose, a four-year case study (2008)(2009)(2010)(2011) was conducted in a small stream (Morcille river) long exposed to high diuron concentrations, increasing from upstream to downstream. Our results show that the ban on diuron in December 2008 resulted in a progressive decrease in its concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
(54 reference statements)
1
11
0
Order By: Relevance
“…Based on the relationship between community tolerance and the intensity of exposure, applying PICT towards one specific compound can determine whether this compound still modulates the measured tolerance. A recent case field survey, based on the study of pesticide biodegradation potential in river sediments, showed that adaptation capacities of microbial communities can be used as an ecological indicator of microbial recovery following a decrease in chronic pesticide exposure (Pesce et al, 2013).…”
Section: Pict Biodiversity and Ecosystem Functionsmentioning
confidence: 99%
“…Based on the relationship between community tolerance and the intensity of exposure, applying PICT towards one specific compound can determine whether this compound still modulates the measured tolerance. A recent case field survey, based on the study of pesticide biodegradation potential in river sediments, showed that adaptation capacities of microbial communities can be used as an ecological indicator of microbial recovery following a decrease in chronic pesticide exposure (Pesce et al, 2013).…”
Section: Pict Biodiversity and Ecosystem Functionsmentioning
confidence: 99%
“…A study showed that 12 out of 15 urban creeks in California were toxic, and sediment pyrethroid pesticide (a replacement for organophosphates for many urban applications) concentrations were sufficient to cause toxicity in amphipod, Hyalella azteca (Amweg et al, 2006). Understanding the pesticide presence and its degradation in sediment environment can provide improved information with regards to the ecological health of a waterbody (Pesce et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a recent study has shown that the ban on diuron in December 2008 has resulted in a progressive decrease in its concentrations in the Morcille River. Thus annual median concentrations recorded at the contaminated station (based on biweekly samples) fell more than fivefold between 2008 (about 110 ng/L) and 2011 (about 20 ng/L), while more than 92 % of water samples collected at the reference station exhibited concentrations below the quantification level of 10 ng/L (Pesce et al 2013). In the present study, the mean diuron concentrations recorded in reference (about 4 ng/L) and contaminated channels (about 28 ng/L) were consistent with concentrations previously observed in the river.…”
Section: Discussionmentioning
confidence: 95%
“…This small shallow river, which has been extensively studied over the last decade , is characterized by a contamination gradient running upstream (reference site) to downstream (contaminated site). In addition, we used an original PICT approach designed to assess changes in the tolerance of phototrophic communities to metals and pesticides, by combining the use of individual toxicants (diuron and copper, which are among the main herbicides and metals detected in the Morcille river, despite diuron being banned in France since December 2008; Pesce et al 2013), and the use of mixtures of organic pesticides and metals directly extracted from the river using passive samplers (i.e., POCIS and diffusive gradient in thin films (DGT)). Based on PICT assessments, our objective was to compare differences in acquired tolerance to metals and organic pesticides between phototrophic biofilm communities previously exposed to raw or filtered contaminated water.…”
Section: Responsible Editor: Philippe Garriguesmentioning
confidence: 99%